UPAYA PENINGKATAN AKSES DAN MUTU PENDIDIKAN: MANAJEMEN PENERIMAAN PESERTA DIDIK BARU DI SMA KOSGORO BOGOR - Herman Lasrin (Jurnal Abdi Insani, 2023)
Education at every level of education begins with the admission of new students in each education unit, both online and offline. The admission of new students is a very important activity in schools, especially private schools, because it is an indicator of the school's success in managing. The purpose of writing this article is to provide comprehensive information and understanding of the efforts made by SMA Kosgoro Bogor in improving access and quality of education through the management of new student admissions. Methods The new student admission activity at SMA Kosgoro Bogor was carried out for six months, which was divided into 2 important parts, namely the socialization period which began in January - April 2023 and the admission of new students in May - July 2023. The results obtained in this activity were the fulfilment of the target of 288 new students of SMA Kosgoro Bogor through various existing pathways such as the achievement pathway for students who have superior academic potential, the championship achievement pathway, the environmental development pathway, the family development pathway for students who come from educational institutions under the Dharma Setia Kosgoro Foundation, the student council chairman pathway, the hafidz Qur'an pathway, and the special pathway for teachers' children. By providing opportunities for prospective new students to join SMA Kosgoro Bogor through various channels available according to predetermined criteria, the quota or target of students has always been met in the last three years.